History of Metals in Colonial America - Mulholland, James A., 1935- (Book collections on Project MUSE., 2015)
The story of the introduction and growth of the technology of metals in the North American colonial period entails significant developments beyond the transfer of the technology from the Old World to the New. In the struggle to create an indigenous industry, in the efforts to encourage and support the work of metals craftsmen, in the defiance of British attempts to regulate manufacturing of metals, the colonial society developed a metals technology that became the basis for future industrial growth. The author traces colonial industrial development from the sixt.